Answer:
(2,2)
Explanation:
1. Find the equation of the function f(x). The graph of this function passes through the points (3,0) and (0,6). Then its equation is
![y-6=(0-6)/(3-0)(x-0)\\ \\y-6=-2x\\ \\y=-2x+6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/j1zy8e1sbyyqfpv3emnzg4xp7urqzn3rgs.png)
2. Find the equation of the inverse function
![f^(-1)(x):](https://img.qammunity.org/2021/formulas/mathematics/middle-school/20c2urgmb4leofz40rbrt710zwkv15q2ja.png)
![y=-2x+6\\ \\y-6=-2x\\ \\x=-(1)/(2)(y-6)\\ \\x=-(1)/(2)y+3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/av9tk9y1q9w7s0ikkh5fe4d82er568d5go.png)
Change x into y and y into x:
![y=-(1)/(2)x+3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6a5qhy9fvjgf37wx1bcyzjo3i5m3go9hcy.png)
3. Find the point of intersection solving the system of two equations:
![\left\{\begin{array}{l}y=-2x+6\\ \\y=-(1)/(2)x+3\end{array}\right.](https://img.qammunity.org/2021/formulas/mathematics/middle-school/9xzquz7llck5sv87hgd25fpl3volpb59nk.png)
Equate right parts:
![-2x+6=-(1)/(2)x+3\\ \\-4x+12=-x+6\\ \\-4x+x=6-12\\ \\-3x=-6\\ \\x=2\\ \\y=-2\cdot 2+6=2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/xdjgjl17mni90v3xl6ckwxk6tawhn1i0f6.png)
Hence, the point of intersection has coordinates (2,2)